Loss of Profilin3 Impairs Spermiogenesis by Affecting Acrosome Biogenesis, Autophagy, Manchette Development and Mitochondrial Organization - Umer, Naila; Arévalo, Lena; Phadke, Sharang; Lohanadan, Keerthika; Kirfel, Gregor; Sons, Dominik; Sofia, Denise; Witke, Walter; Schorle, Hubert (Frontiers in Cell and Developmental Biology, 2021)
Profilins (PFNs) are key regulatory proteins for the actin polymerization in cells and are encoded in mouse and humans by four Pfn genes. PFNs are involved in cell mobility, cell growth, neurogenesis and metastasis of tumor cells. The testes specific PFN3 is localized in the acroplaxome-manchette complex of developing sperm. We demonstrate, that PFN3 further localizes in the Golgi complex and proacrosomal vesicles during spermiogenesis, suggesting a role in vesicle transport for acrosome formation. Using CRISPR/Cas9 genome editing we generated mice deficient for Pfn3. Pfn3-/- males are sub-fertile displaying a type II-globozoospermia. We revealed, that Pfn3-/- sperm display abnormal manchette development leading to an amorphous sperm head shape. Additionally, Pfn3-/- sperm showed reduced sperm motility resulting from flagellum deformities. We show, that acrosome biogenesis is impaired starting from the Golgi phase and mature sperm seems to suffer from a cytoplasm removal defect. RNA-seq analysis revealed an upregulation of Trim27 and downregulation of Atg2a. As a consequence, mTOR was activated and AMPK was suppressed resulting in the inhibition of autophagy. This dysregulation of AMPK/ mTOR affected the autophagic flux which is hallmarked by LC3B accumulation and increased SQSTM1 protein levels. Autophagy is involved in proacrosomal vesicle fusion and transport to form the acrosome. We conclude that this disruption leads to the observed malformation of the acrosome. TRIM27 is associated with PFN3 as determined by co-immunoprecipitation from testis extracts. Further, actin related protein ARPM1 was absent in the nuclear fraction of Pfn3-/- testes and sperm. This suggests, that lack of PFN3 leads to destabilization of the PFN3-ARPM1 complex resulting in the degradation of ARPM1. Interestingly, in the Pfn3-/- testes, we detected increased protein levels of essential actin regulatory proteins, cofilin-1 (CFL1), cofilin-2 (CFL2) and actin depolymerizing factor (ADF). Taken together, our results reveal the importance for PFN3 in male fertility and implicates this protein as a candidate for male factor infertility in humans.